Preparation of SiC/Ti(C,N) Ceramic Fibers by Sol-Gel Process and Carbothermal Reduction-Nitridation Reaction - Song, Qiu-Sheng; Xu, Shun; Zhang, Kai (Asian Journal of Chemistry, 2011)
Using tetraethoxy silane, tetrabutyl titanate and sucrose as raw materials, TiO2/SiO2/sucrose hybrid fibers were prepared via sol-gel method associated with drawing process. The carbothermal reduction-nitridation reaction of the hybrid fibers was carried out under nitrogen atmosphere in the temperature range from 800-1500 ºC. Fourier transfer infrared spectroscopy, thermalgravimetry, X-ray diffraction and scanning electron microscopy were employed to investigate the microstructure variation and reaction mechanism of the hybrid fiber in the carbothermal reduction-nitridation process. The results showed that Ti (C, N) formed at ca. 1200 ºC and the formation temperature of SiC was about 1400 ºC. SiC/Ti (C, N) composite ceramic fibers were finally produced at 1500 ºC.